Can You Fish in a Pandemic? An Overview of Recreational Fishing Management Policies in North America During the COVID‐19 Crisis. Issue 2 (18th December 2020) - Paradis, Yves; Bernatchez, Simon; Lapointe, Dominique; Cooke, Steven J.
Abstract : Facing challenges of the COVID‐19 pandemic, government agencies had to quickly react and provide guidelines for outdoor activities such as recreational fishing. Here we review information provided by provincial and state natural resource management agencies in North America during the March–April 2020 period to collate freshwater fishing regulations implemented during the pandemic. Among the 63 jurisdictions for which information was collected, 92% of jurisdictions kept the recreational fishing season open, asking anglers to practice social distancing at all times. Although recreational fishing was open in most jurisdictions, specific measures for anglers and for the fishing industry (e.g., fishing guides) were enforced to comply with public health rules. Some management agencies altered stocking practices, restricted fishing by non‐residents, withdrew permits for competitive angling events, and instituted restrictions on the charter and guide industry. This overview of fishing regulations in North America in the context of a major pandemic provides fisheries managers a portrait of some measures taken by other jurisdictions.